Observatories of the Southwest : a guide for curious skywatchers - Isbell, Douglas, 1964- (University of Arizona Press, 2009)
With its clear skies and low humidity, the southwestern United States is an astronomer's paradise where observatories like Kitt Peak have redefined the art of skywatching. The region is unique in its loose federation of like-minded research outposts and in the quantity and diversity of its observatories--places captured in this unique guidebook.